Imobilisasi silika ke dalam TiO2 untuk fotokatalis - Joice Caroles (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Modification of TiO2 photocatalyst with SiO2 absorbent has been performed. Modification is done by immobilizing SiO2 into TiO2. Photocatalyst of TiO2-SiO2 result from immobilization, then analyzed using SEM-EDS instrument. The analysis was performed to see the immobilized silica. The results of the analysis showed that the silica content of 47.90% immobilized on TiO2 photocatalyst.